2002
DOI: 10.1093/bja/88.2.298
|View full text |Cite
|
Sign up to set email alerts
|

Infected mediastinitis secondary to perforation of superior vena cava by a central venous catheter

Abstract: We describe the first case of infected mediastinitis associated with central venous catheter insertion. The rare occurrence of this complication may be explained by the fact that it results from central venous catheter-related bloodstream infection and catheter perforation of superior vena cava. The symptoms of this complication (chest pain, dyspnoea) are not specific. Diagnosis should be confirmed by chest x-ray and computerized tomography which show hydromediastinum and pleural effusion. Removal and subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 13 publications
1
20
0
1
Order By: Relevance
“…5 An infectious source can lead to bacterial mediastinitis, complicating vascular perforation by a CVC. 1 In our case, the sudden onset of respiratory insufficiency 6 days after placement of a CVC, the lack of fever, and the negative results of cultures suggest, as in other reported cases, that leakage of parenteral nutritional formula from the CVC migrated into the mediastinum, causing chemical mediastinitis. 4 The lack of blood in the pleural effusion and the mediastinum, as in our case, has been reported previously.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…5 An infectious source can lead to bacterial mediastinitis, complicating vascular perforation by a CVC. 1 In our case, the sudden onset of respiratory insufficiency 6 days after placement of a CVC, the lack of fever, and the negative results of cultures suggest, as in other reported cases, that leakage of parenteral nutritional formula from the CVC migrated into the mediastinum, causing chemical mediastinitis. 4 The lack of blood in the pleural effusion and the mediastinum, as in our case, has been reported previously.…”
Section: Discussionsupporting
confidence: 71%
“…Previous studies 1,5 have indicated that the risk of perforation is greater with left-sided CVCs than with right-sided CVCs. The predisposition of catheters inserted through the left subclavian or left internal jugular vein to perforate the vessel probably is due to the horizontal orientation of the left brachiocephalic vein.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…7 The more perpendicular the catheter tip to the wall of the vein, the greater the risk of perforation. 6,8,9 Catheters inserted through the left subclavian or internal jugular vein are more likely to cause perforation, because the innominate vein forms a right angle to the SVC and the catheter tip may be positioned against the lateral wall of the SVC with a wide angle. 4,6,8,10 In conclusion, any unexplained respiratory deterioration should arouse suspicion of catheter erosion and clinicians should recognize the development of a pleural effusion as a potential delayed complication, days after apparently successful central venous catheter placement.…”
mentioning
confidence: 99%